(untitled) (International Journal of Engineering and Computer Science, 2014)
We review structures for microwave containing ‘left-handed’ metamaterials that are artificial composites with simultaneously negative effective permittivity and permeability which achieve negative values of refractive index and then we discuss some of the salient electromagnetic features of these metamaterials. This is followed by the description of some of the ideas regarding potiential future applications of metamaterials in devices and components.